Fantástico y grotesco en los Cuentos del exilio de Antonio Di Benedetto (Altre Modernità, 2019)
In the stories that make up the collection Cuentos del Exilio (1983), the forces of separation that are implied in exile, the need to believe in the possibility of returning to live in another place and time, the pain of distance and the memories of violence suffered during 17 months of detention, produce, in Antonio Di Benedetto, a hybrid writing in which irony, grotesque and metaliterature are intertwined to generate a fiction that reveals a secret thought: On one hand, the possibility through language to subvert the conception of the world and build an anti-system that contradicts the traditional linearity of time; on the other, the ineffectiveness of the same instruments in relation to the existential condition of man.